2016
DOI: 10.1016/j.ccell.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Chromosome 8p Governs Tumor Progression and Drug Response by Altering Lipid Metabolism

Abstract: Large-scale heterozygous deletions are a hallmark of cancer genomes. The concomitant loss of multiple genes creates vulnerabilities that are impossible to reveal through the study of individual genes. To delineate the functional outcome of chromosome 8p loss of heterozygosity (LOH), a common aberration in breast cancer, we modeled 8p LOH using TALEN-based genomic engineering. 8p LOH alters fatty acid and ceramide metabolism. The shift in lipid metabolism triggers invasiveness and confers tumor growth under str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
149
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 41 publications
6
149
2
Order By: Relevance
“…It has been recently shown that large-scale loss of chromosome material in cancer cells can disturb multiple signaling pathways and produce phenotypes distinct from those arising through loss of a single gene (46). We performed gene ontology (GO) analyses of the differentially expressed mRNAs and of the mRNA targets of the differentially expressed miRs to test whether genes involved in specific biologic processes are enriched in signatures associated with loss of the entire chromosome 7.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently shown that large-scale loss of chromosome material in cancer cells can disturb multiple signaling pathways and produce phenotypes distinct from those arising through loss of a single gene (46). We performed gene ontology (GO) analyses of the differentially expressed mRNAs and of the mRNA targets of the differentially expressed miRs to test whether genes involved in specific biologic processes are enriched in signatures associated with loss of the entire chromosome 7.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies to establish the consequences of these alterations on HLA class I antigen processing and presentation are ongoing. One hypothesis is that while none of these events alone are sufficient to down-modulate antigen presentation, multiple hits together in the same pathway could have this effect similar to how hemizygous loss of multiple contiguous tumor suppressor genes can affect tumorigenesis (41,42). Further supporting the potential for a role of defective antigen processing and presentation defects in mediating resistance to ICIs, we found that three out of five PDXs generated from ICI-resistant tumors exhibited B2M downregulation and two of these also had either loss or barely detectable levels of cell surface HLA class I expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cai et al (2016) created isogenic derivatives of MCF 10A, a human mammary epithelial cell line, with a defined hemizygous deletion in chromosome 8p by TALEN-mediated engineering. Surprisingly, although this SCNA has been implicated as an early event during breast tumorigenesis, it had little impact on transformation capacity alone or with established driver genes.…”
mentioning
confidence: 99%